INKLUSIVITAS SEBAGAI PERWUJUDAN MARTABAT MANUSIA DALAM PERSPEKTIF ETIS FRATELLI TUTTI - Pabubung, Michael Reskiantio; Harsono, Harsono (Jurnal Teologi (Journal of Theology), 2024)
Inclusivity is a principal value in togetherness which is currently being eroded by the emergence of narrow nationalism accompanied by fanaticism spreading in various corners of the world. Many countries build fortresses to separate themselves from others because of excessive suspicion of others. Furthermore, religions have been inseparable from the strongholds that increasingly separated one from the other. This phenomenon received exceptional attention from Pope Francis in the Fratelli Tutti encyclical which was written in loving language to encourage fraternity. One of the frequently appearing keywords in this encyclical is human dignity or dignity of the human person. How did Pope Francis talk about the inclusivity in Fratelli Tutti concerning human dignity? Through qualitative method using literature analysis techniques, the authors answered this main question from Fratelli Tutti’s ethical perspective through three focal inquiries, i.e., Fratelli Tutti, inclusivity, and human dignity. The novelty of this research lies in the analysis that seeks the comprehensive relationship between inclusivity and human dignity to conceptual thinking enrichment.